Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1975
DOI: 10.1002/app.1975.070190112
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic charge acceptance and decay of powder coating particles

Abstract: SynopsisTechniques have been developed to measure the acceptance and decay of electrostatic charge on a wide variety of powder coatings. The measurement of the initial charge carried by the powder was affected by the amount of powder deposited. The decay of charge occurred within four time scales: (1) 1 sec, electron loss to air and to the metallic substrate; (2) 1 to 5 sec, electron flow to neutralize induced positive charge; (3) 5 to 100 sec, rapid decay from powder; and (4) 1,OOO to 10,000 sec, very long te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Although several charge-decay models of high-polymer powders Ž . Cheever et al;1973;Golovoy and Colvin, 1975 have been suggested, it is not yet clear whether these charge-decay models are suitable for organic pigments.…”
Section: Introductionmentioning
confidence: 99%
“…Although several charge-decay models of high-polymer powders Ž . Cheever et al;1973;Golovoy and Colvin, 1975 have been suggested, it is not yet clear whether these charge-decay models are suitable for organic pigments.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum acceptance potential observed in polystyrene layer under controlled conditions was 900 V, which was found to be very stable with a half decay time of a few days. According to SUGAI et al [3] and CHEEVER [4] the rate of charge decay from corona charged polymer layers is strongly influenced by the ambient humidity. The effect of variation in humidity on electrothermographic parameters of various polymer l'ilms has already been studied [2].…”
Section: Introductionmentioning
confidence: 99%